PENINGKATAN KEMANDIRIAN DAN KREATIVITAS SISWA SMU DI KOTA JEMBER - H SOEPARMAN (Jurnal Kependidikan, 2002)
Abstract The objective of this study was to find out the development of the senior high school students’ independency and creativity. The subjects were 150 students of the senior high school at Jember Minicipality area, consisting of 50 students of the first year, 50 students of the second year and 50 students of the third year. The data were collected through a questionnaire and a verbal test, and then analyzed by using t-test. It was assumed that the scores on the questionnaire and the test depended on the students; grade only. Based on this assumption, it could be concluded that the students’ independence and creativity developed from the first grade to the second grade, and from the second grade to the third grade. Keywords: students’ independence, students’ creativity